Household Financial Management Behavior During Pandemic Covid 19 - Liliek Nur Sulistiyowati; Robby Sandhi Dessyarti (Widya Cipta - Jurnal Sekretari dan Manajemen, 2022)
The COVID-19 pandemic has had a tremendous impact on the economic sector in Indonesia, including changes in the composition of household finances. This study aims to assess the impact of the COVID-19 pandemic on household financial management. This study takes the target population of households living in Madiun and its surroundings. The sampling technique used was cluster random sampling. The number of samples is 384 respondents who are proportionally distributed into 5 (five), namely Madiun City, Madiun Regency, Ponorogo Regency, Magetan Regency, and Ngawi Regency, so that the sample taken can generalize the household population in Madiun and its surroundings. Methods of data collection include direct interviews using structured questionnaires. The research approach uses a quantitative approach using one-way ANOVA analysis techniques.The conclusion obtained from the results of the study is that the COVID-19 pandemic has a significant effect on household financial management behavior in Madiun and its surroundings. The average behavior related to household financial management shows that before the COVID-19 pandemic it was 83.27, while during the COVID-19 pandemic it was 73.34. These results show that household economic activities are carried out more often before the pandemic than during the pandemic.